First Principle DFT + U Calculations for the Optoelectronic Properties of Cu and C-Cu co-doped TiO2Anatase Model - Ullah, F. (Asian Publication Corporation, 2022)
The metal-cations and non-metal anions mono-doped titanium dioxide (TiO2) systems have shown limited success as an efficient photocatalyst for various photocatalytic applications. Instead, the co-doping of TiO2with metal and non-metal dopants is transpired as an effective doping approach to reduce the wide bandgap of the TiO2and harvest a greater amount of the visible solar spectrum. Herein, a computational study was systematically performed to develop an efficient carbon-copper (C-Cu) co-doped TiO2anatase system and compared its optoelectronic characteristics with the copper (Cu) mono-doped TiO2system. The structural properties simulated with Perdew-Burke-Ernzerhof assisted generalized gradient approximation (GGA + PBE) whereas the electronic and optical properties with Hubbard's modified (GGA + U) approximation. The electronic band structure and density of states plots display reduced bandgap energy of 2.30 eV for the C-Cu co-doped TiO2anatase model in comparison to Cu mono-doped TiO2anatase model. Moreover, the absorption spectra display a redshift of the optical absorption edge up to 515 nm for the co-doped system. Overall, the DFT work provide clear insights and predictions that the C-Cu co-doped TiO2anatase model has an efficient bandgap narrowing with a significant redshift of the optical absorption edge in comparison to Cu mono-doped TiO2model. Â© 2022 Chemical Publishing Co.. All rights reserved.